Unravelling drought stress adaptation in sugarcane interspecific hybrids: A multi-level analysis - Lakshmi Kasirajan; Sheelamary Sebastiar; Ramvannish Muthukumar; Rachel Lissy Vargheese; Karpagam Elumalai; Keerthana Kamaraj; Rabisha Valiyaparambth; Suganya Angannan; Annadurai Ayyadurai; Gomathi Raju; Selvi Athiappan; Devakumar Krishnamoorthy; et al. (PLoS ONE, 2025)
Drought stress, a major abiotic stress, severely limits sugarcane productivity through adversely altered cellular processes. Identifying key traits linked to physiological and biochemical responses during water stress and recovery is vital for screening and breeding drought stress-tolerant varieties. The present study assessed 18 sugarcane genotypes based on morpho-physiological, biochemical, and molecular changes during drought stress and at stress recovery in a complete randomized block design. Cane height, number of internodes, Soil Plant Analytical Development (SPAD) index, Leaf Area Index (LAI), Relative Water Content (RWC), Nitrate Reductase (NR), and proline were positively correlated to drought stress. Among the genotypes studied, AS-04-1687, AS-04-635, Co 86032, Co 85019, CoM 0265, AS-04-2097, and AS-04-245 were identified as potential clones with high potential for drought stress tolerance in sugarcane. Expression profiling of ten stress-induced genes, namely NAC, MYB59, peroxidase, GST (glutathione transferase), GLY I (glyoxylase I), GLY III (glyoxylase III), RAB (response to abscisic acid), CesA3 (cellulose synthase), heat shock proteins, and stress-related proteins in sugarcane stem tissues under drought-stressed conditions revealed significant differences between tolerant and susceptible genotypes. The interspecific hybrid, AS-04-1687, outperformed for all the genes under drought stress conditions and could be a potential donor in further drought tolerance breeding programmes. We have also cloned and characterised drought stress-induced transcription factor MYB59 (a negative regulator of Ca + signalling), which could be used in genetic engineering programmes for the development of drought stress-tolerant genotypes.